Characterisation of nano-grains in MgB2 superconductors by transmission Kikuchi diffraction. (May 2015) - Wong, D.C.K.; Yeoh, W.K.; Trimby, P.W.; De Silva, K.S.B.; Bao, P.; Li, W.X.; Xu, X.; Dou, S.X.; Ringer, S.P.; Zheng, R.K.
Abstract : We report the first application of the emerging transmission Kikuchi diffraction technique in the scanning electron microscope to investigate nano-grain structures in polycrystalline MgB2 superconductors. Two sintering conditions were considered, and the resulting differences in superconducting properties are correlated to differences in grain structure. A brief comparison to X-ray diffraction results is presented and discussed. This work focusses more on the application of this technique to reveal grain structure, rather than on the detailed differences between the two sintering temperatures.